The Effect of Entrepreneurship Education and Digital Literacy on the Interest in Entrepreneurship on Senior High School Students in Mojokerto with Opportunity Recognition as a Mediating Variable - Sunariyadi Sunariyadi; Naswan Suharsono; Titis Shinta Dhewi (International Journal of Business and Quality Research, 2025)
This study aims to analyze the effect of entrepreneurship education and digital literacy on entrepreneurial interest, with opportunity recognition as a mediating variable. This study uses a quantitative approach with a survey method through hypothesis testing. The research sample involved 358 senior high school students in grade XII in the Mojokerto area. Data analysis was performed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results of this study indicate that entrepreneurship education and digital literacy have a significant and positive effect on opportunity recognition. In addition, opportunity recognition has a significant and positive effect on entrepreneurial interest. However, entrepreneurship education and digital literacy do not have a significant or negative effect on entrepreneurial interest. Entrepreneurship opportunity recognition mediates the effect of entrepreneurship education and digital literacy on entrepreneurial interest. Students do not have an interest in entrepreneurship if the recognition of entrepreneurial opportunities is not included in entrepreneurship education and digital literacy in senior high schools in the Mojokerto region. The implications of this study can help public high school educational institutions in Mojokerto to improve entrepreneurial projects and family support for students to realize entrepreneurial behavior in line with the needs of today's business world.